Color and tone color: audiovisual crossmodal correspondences with musical instrument timbre - Lindsey Reymore; Lindsey Reymore; Delwin T. Lindsey; Delwin T. Lindsey (Frontiers in Psychology)
Crossmodal correspondences, or widely shared tendencies for mapping experiences across sensory domains, are revealed in common descriptors of musical timbre such as bright, dark, and warm. Two experiments are reported in which participants listened to recordings of musical instruments playing major scales, selected colors to match the timbres, and rated the timbres on crossmodal semantic scales. Experiment A used three different keyboard instruments, each played in three pitch registers. Stimuli in Experiment B, representing six different orchestral instruments, were similar to those in Experiment A but were controlled for pitch register. Overall, results were consistent with hypothesized concordances between ratings on crossmodal timbre descriptors and participants’ color associations. Semantic ratings predicted the lightness and saturation of colors matched to instrument timbres; effects were larger when both pitch register and instrument type varied (Experiment A) but were still evident when pitch register was held constant (Experiment B). We also observed a weak relationship between participant ratings of musical stimuli on the terms warm and cool and the warmth-coolness of selected colors in Experiment B only. Results were generally consistent with the hypothesis that instrument type and pitch register are related to color choice, though we speculate that these associations may only be relevant for certain instruments. Overall, the results have implications for our understanding the relationship between music and color, suggesting that while timbre/color matching behavior is in many ways diverse, observable trends in strategy can in part be linked to crossmodal timbre semantics.